Liver steatosis in brain death donors - D. V. Voronov; M. G. Minina; A. K. Chomaev; I. M. Iljinsky; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
Aim. To study the frequency of fatty hepatosis in liver biopsies of consecutive brain death donors before cold preservation. Materials and methods. Liver biopsies (before cold preservation) of 300 consecutive donors with brain death were studied. Histological preparations were stained with hematoxylin and eosin, and tricolor Masson staining was performed. Results. The frequency of different degrees of fat hepatosis in men and women did not differ significantly (>0.05). Fat dystrophy of hepatocytes was absent in more than half of the cases (n = 182; 60.7%). A slight degree of fatty degeneration was diagnosed in 57 (19,0%) donors. In total, 239 (79.7%) donor livers were absolutely suitable for transplantation. Moderate degree of steatosis, which is associated with early biliary complications, was detected in 18 (6.0%) cases, and severe degree, which is a contraindication to the use of the organ for transplantation, was detected in 43 (14.3%) cases. Conclusion. Before cold preservation, liver from brain death donors is relatively rarely unsuitable for transplantation.